The Role of Security Measures in Crime Prevention - Jovašević, Dragan (Zbornik Instituta za kriminološka i sociološka istraživanja, 2010)
All contemporary states apply a variety of measures, means and methods in order to suppress different forms and aspects of crime. The system of criminal sentences particularly stands out within these measures. It represents the collection of all compulsory criminal-legal measures that are stipulated by the law and imposed by the court in a legally prescribed criminal procedure against the perpetrator of a criminal offence, with the aim to prevent the commission of criminal offences. Among other criminal sentences, security measures have a special place, role, nature, significance and characteristics. The reason for these measures to be applied rests upon offender’s hazardous condition, which has resulted in his criminal behavior. The enforcement of these measures is intended to achieve special preventive goals through the elimination of states and conditions that can once more encourage such a person to commit criminal offences. This paper discusses the term and the characteristics of security measures as well as the conditions for their enforcement and execution in the criminal law of the Republic of Serbia, from both theoretical and practical aspects.